Meninjau Kembali Penyelesaian Sengketa Tanah Ulayat Berlandaskan Asas Musyawarah Mufakat: Studi Putusan Nomor 50/Pdt.G/2017/Pn.Son - Susanto, Marchel Christoper Farrel; Lumban Gaol, Heru Saputra (Darma Cendika Catholic University, 2025)
Settlement of ulayat land disputes highlights the tension between the national legal system, which prioritizes formal legality, and customary law, which upholds spiritual, communal, and cultural values. This research focuses on the principle of consensus-based deliberation (musyawarah mufakat) as a dispute resolution approach that emphasizes collective justice, based on a study of Judgement Number 50/Pdt.G/2017/Pn.Son between the Moi Indigenous Peoples and PT Bank Pembangunan Daerah Papua. The research employs a normative juridical method with statutory, conceptual, and case study approaches. The analysis shows that unilateral monetary compensation fails to represent the religio-magical and social values inherent in ulayat land. The principle of musyawarah mufakat, although recognized in Pancasila and customary legal systems, has not been fully integrated into the resolution process through state judicial institutions. A deliberation-based approach offers an impartial, more restorative alternative that aligns with the needs of indigenous communities in preserving their social and cultural existence.